2021
DOI: 10.1002/admi.202100247
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Superhydrophobic Surfaces: Healing Principles and Applications

Abstract: Superhydrophobic surfaces have already been applied in anti‐fouling, water‐oil separation, liquid transportation, etc. Surfaces can be defined as superhydrophobic surfaces once they can support a water droplet with its spherical shape maintained and accompanied by an apparent contact angle larger than 150° and a rolling‐off angle below 10°. Such water repellent property is achieved by the synergetic action of hierarchical structures and the low‐surface energy of the substances constructing the surface. Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 106 publications
0
46
0
Order By: Relevance
“…Consequently, attention should be given to coatings that could combine superhydrophobicity with other important properties. As a result of their precise micro-/nanoscale architectures, superhydrophobic coatings tend to be fragile and lose their superhydrophobicity once subjected to mechanical wear [258]. Many workers studied the effect of sandpaper abrasion on the hydrophobicity of their coatings, which almost always resulted in a consequent decrease in the water contact angle.…”
Section: Normative Aspectsmentioning
confidence: 99%
“…Consequently, attention should be given to coatings that could combine superhydrophobicity with other important properties. As a result of their precise micro-/nanoscale architectures, superhydrophobic coatings tend to be fragile and lose their superhydrophobicity once subjected to mechanical wear [258]. Many workers studied the effect of sandpaper abrasion on the hydrophobicity of their coatings, which almost always resulted in a consequent decrease in the water contact angle.…”
Section: Normative Aspectsmentioning
confidence: 99%
“…Apart from this strategy, the self-healing function of organisms in nature provides a more miraculous solution for prolonging the lifespan of superhydrophobic surfaces. , In particular, the superhydrophobic micro/nanostructures of the nature plants can re-grow by harvesting energy from sunlight. In the past few years of study, it has been revealed that the self-healing property of the artificial superhydrophobic surfaces can be realized either by the releasing surface chemistry or the reforming surface micro/nanostructures. The former method can be easily realized by storing the low-surface-energy materials inside the hierarchical micro/nanostructures and then releasing them onto the damaged surface during the self-healing process, while the latter method can be carried out by regenerating the hierarchical micro-/nanostructures again under an external environment, which is comparatively difficult. Although some advances have been achieved for the latter method, there are still some problems.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, intrinsic SHSMs designate a wide variety of systems with autonomous or induced healing ability, which requires an external stimulus, including light [ 15 ], thermal or temperature [ 16 ], laser beam [ 17 ], magnetic [ 18 ], chemical [ 19 ], electricity [ 20 ] or catalytic agent [ 21 ], and can executed itself to heal after damaged. At present, many research groups have been actively engaged in the research of SHSMs [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%